RISK FACTORS OF DAMAGE OF THE CARDIOVASCULAR SYSTEM IN PATIENTS WITH PRIMARY OSTEOARTHRITIS WITH IDENTIFIED CORONARY ATHEROSCLEROSIS - S. M. Tsvinger; A. V. Govorin; O. O. Portyannikova; E. N. Romanova (SINAPS LLC, 2018)
The aim of the research is to assess risk factors of damage of the cardiovascular system in patients with primary osteoarthritis with identified coronary atherosclerosis.Materials and methods. 52 patients at the mean age 41 [34; 52] were involved in the study. Therewere 37 womenand 15 menamongthem. Planned contrast study of the coronary arteries (on the apparatus ALLURAXperFD20 Philips) were performed to all patients. As a result, hemodynamically insignificant (less than 50%) atherosclerotic stenosis of the heart vessels was verified in this group. In all patients were determined such indicators as: height, weight, waist circumference with the calculation of body mass index by Kettle`s method. The questionnaire was used to assess the presence of risk factors for development of cardiovascular diseases, such as: smoking, family history of cardiovascular diseases, hypodynamia. In addition, all patients had daily monitoring of arterial pressure by the device «Kardiotechnika- 07-AP-3», clinical and biochemical blood tests and the total cardiovascular risk was calculated.Results. Each patient had from 1 to 6 risk factors of cardiovascular diseases, the median was [25-th; 75-th percentiles] 3 [2; 5]. In the group of women family history of cardiovascular diseases, hypodynamia and hypertension met more often the in the group of men (р=0,002). Men with higher frequency demonstrated the presence of bad habits (smoking), high levels of triglycerides and low-density lipoproteins (p=0.0001). The correlation analysis revealed that the incidence of hypertension, hypodynamia and dyslipidemia was associated with the duration of osteoarthritis, the intensity of pain according to visual analog scale and the number of affected joints.Conclusion. The presense of generalized subclinical inflammation in patients with ostheoarthritis together with the classic risk factors of development of cardiovascular diseases, probably mediates the early beginning of atherosclerosis in this category of patients.